Unveiling stroke: biomarkers and diagnostic strategies - Wadan, Al-Hassan Soliman; Mohamed, Wael Mohamed Yousef (Springer, 2024)
Stroke, a leading cause of sickness and death worldwide, is difficult to diagnose and treat. This book chapter examines biomarkers and diagnostic methods’ role in stroke research. This article discusses stroke biomarkers, including proteins, nucleic acids, metabolites, and cellular components, and their ability to detect strokes early, evaluate risk, and predict outcomes. The chapter shows how multimodal approaches may accurately diagnose and classify strokes by combining clinical assessments with biomarker technology. Additionally, it addresses biomarker standardization, timing, and stroke differentiation from similar conditions. This chapter aims to increase stroke pathophysiology understanding and encourage the development of new diagnostic tools and personalized treatment methods to improve patient outcomes. Critically assessing study outcomes and investigating prospects will accomplish this.